Themes of contemporary art visual art after 1980 - Robertson, Jean 1950-; McDaniel, Craig (Oxford University Press, 2017)
"Offering a unique thematic approach to recent art history, Themes of Contemporary Art: Visual Art after 1980, fourth edition, focuses on eight central ideas recurring in art over the past few decades: identity, the body, time, memory, place, language, science, and spirituality. This thought-provoking volume features over 200 full-color images of artworks that exemplify a wide variety of materials, techniques, theoretical viewpoints, and stylistic approaches, by artists from diverse ethnic, cultural, and geographic backgrounds. Its concise, engaging, and accessible narrative challenges readers to think actively and critically about ideas expressed in contemporary art." -- Provided by publisher.